2021
DOI: 10.1080/14680777.2021.1948885
|View full text |Cite
|
Sign up to set email alerts
|

Say no to shame, waste, inequality—and leaks! Menstrual activism in the market for alternative period products

Abstract: For decades, advertisements for mainstream menstrual products have been criticised for upholding harmful menstrual taboos. Meanwhile, the range of alternative products has increased, and menstrual cups, discs, underwear, and cloth pads have become more easily available. This article examines how online promotional materials of alternative products relate to the menstrual taboo and other concerns raised by menstrual activists. Based on thematic analysis of seven websites selling alternative period products, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This individualising discourse in the coverage accentuated the notion that products are the answer to period poverty; the more you consume or donate, the more period poverty will be solved. This is similar to how websites and blogs of alternative period products market themselves under popular feminism (Koskenniemi, 2021). This mentality underscores that while menstruation has long been hidden, products are increasingly central to menstruation, and using them is now positioned as empowering and 'promising freedom through "feminist capitalism"' (Røstvik, 2022: 164; see also Koskenniemi, 2021).…”
Section: Shifting the Focus To Products And Individualsmentioning
confidence: 82%
See 1 more Smart Citation
“…This individualising discourse in the coverage accentuated the notion that products are the answer to period poverty; the more you consume or donate, the more period poverty will be solved. This is similar to how websites and blogs of alternative period products market themselves under popular feminism (Koskenniemi, 2021). This mentality underscores that while menstruation has long been hidden, products are increasingly central to menstruation, and using them is now positioned as empowering and 'promising freedom through "feminist capitalism"' (Røstvik, 2022: 164; see also Koskenniemi, 2021).…”
Section: Shifting the Focus To Products And Individualsmentioning
confidence: 82%
“…I have shown that period poverty became an issue that needed public attention as a result of the continued dismantling of the welfare state and individualising of poverty, an escalation of 'popular feminism' (Banet-Weiser, 2018) and feminist activism around menstruation, as well as high-profile individuals (celebrities, MPs, royals etc) supporting period poverty through philanthropy. The analysis highlighted the subject of period poverty was often a schoolgirl, following other media representations (Koskenniemi, 2021;Tomlinson, 2021). While it is important to address whether schoolgirls are experiencing period poverty, this rendering of period poverty ultimately created 'deserving' subjects and continues to individualise poverty.…”
Section: Discussionmentioning
confidence: 99%
“…esteem (McKay, 2021). The act challenges menstrual stigma, but it reinforces the contemporary 'double-bind' of openly discussing periods while simultaneously reinforcing old tropes of concealment (Koskenniemi, 2021).…”
Section: The Scottish Actmentioning
confidence: 99%
“…Menstrual products have been advertised to appeal to certain markets, but menstruators also incorporate or reject use of them based on personal beliefs. 'Teenager', 'laborer', 'environmentalist', or 'non-binary person', for example, are identities with whom menstrual product companies have sought to align at different historical moments (Brumberg, 1998;Koskenniemi, 2021;.…”
Section: Personal Identitymentioning
confidence: 99%
“…MHM research could have gone in multiple directions, given the diversity of cultural and religious practices related to menstruation around the world (Buckley & Gottlieb, 1988;van de Walle & Renne, 2001) and the recent adoption of some LMIC menstrual practices in Western countries (Castro, 2020;Koskenniemi, 2021). In the United States, for example, decades after switching to disposable products to manage their menstruation, young women are now demanding cloth absorbents as an environmentally sustainable alternative (Makhijani, 2022).…”
Section: Producing a Problem At Scale Through Sciencementioning
confidence: 99%